The benefits of swimming training in dealing with stress in school-age children: A quasi-experimental study in Bali - Dewi, Komang Ayu Krisna; Ilmy, Shofi Khaqul (Promotion and Prevention in Mental Health Journal, 2022)
Swimming is a popular water sport for the community. This sport is considered very fun and suitable for anyone regardless of age. Swimming has various benefits, including improving psychosocial conditions in school-age children during the COVID-19 pandemic. This study aims to determine the effect of swimming training on reducing stress in school-age children. This quasi-experimental study was conducted using a one-group pretest-posttest design approach, which was conducted on 30 elementary school students registered at the Jalak Bali Swimming Club, Jembrana, Bali who have met the inclusion criteria. The training program was developed based on the principles of the Bompa training and the stress score was measured using a 14-item PSS-C questionnaire on pretest and post-test. then the data were analyzed using the paired t-test to determine the effect of swimming exercise. The results of these tests can be concluded that swimming training has a significant effect on reducing stress in school-age children (sig. value < 0.05). Furthermore, there is a decrease in stress scores of 3,467 from the results of the pretest to the post-test. Swimming training can reduce stress for school-age children. Swimming sports activities can be an alternative for parents or teachers in dealing with stress to improve the mental health of school-age children.